Linear and star-shaped poly(2-ethyl-2-oxazine)s. Synthesis, characterization and conformation in solution. (5th August 2021) - Smirnova, Anna; Kirila, Tatyana; Blokhin, Alexey; Kozina, Nina; Kurlykin, Mikhail; Tenkovtsev, Andrey; Filippov, Alexander
Graphical abstract: Highlights: Star-shaped poly(2-ethyl-2-oxazine)s were synthesized using grafting-onto approach. Samples poly(2-ethyl-2-oxazine)s were obtained in a wide ranges of molar masses. Chains of poly(2-ethyl-2-oxazine) are flexible with Kuhn segment length 1.5 nm. Star-shaped poly(2-ethyl-2-oxazine)s have high intramolecular density. Abstract: Linear and star-shaped poly(2-ethyl-2-oxazine)s have been synthesized. The star core was a calix[4]arene. The linear polymers and star arms were prepared by the cationic ring-opening polymerization of 2-ethyl-2-oxazine. The grafting-onto approach was used to synthesize the polymer stars. Molar masses were in the range from 2500 to 38, 000 g⋅mol −1 for linear samples and from 5100 to 23, 000 g⋅mol −1 for stars. Hydrodynamic and conformational behavior of synthesized polymers were investigated by molecular hydrodynamics and optics methods in dilute solutions in 2-nitropropane. It was shown that linear poly(2-ethyl-2-oxazine) is a flexible-chain polymer with length of statistical Kuhn segment 1.5 nm and macromolecular diameter 0.5 nm. The molecules of star-shaped poly(2-ethyl-2-oxazine) are characterized by compact structure and high intramolecular density. The arms are coiled to shield the calix[4]arene core from the solvent. The arm lengthening leads to a decrease in the intramolecular density and shape symmetry of the star-shaped molecules.